Effect of long COVID-19 syndrome on health-related quality of life: a cross-sectional study - Rodrigues, Arthur Nascimento; Paranhos, Alna Carolina Mendes; da Silva, Livia Caroline Machado; Xavier, Stanley Soares; Silva, Camilla Costa; da Silva, Rosilene; de Vasconcelos, Lidiane Assunção; Peixoto, Ivonete Vieira Pereira; Panzetti, Tatiana Menezes Noronha; Tavares, Priscila Rodrigues; Reis, Cíntia de Sousa; Launé, Beatriz Freitas; et al. (Frontiers in Psychology, 2024)
Purpose This study aimed to assess the association of anxiety, headache, and insomnia on the QoL of patients with long COVID-19. Methods We conducted a cross-sectional survey between August 2020 and March 2023. A total of 200 participants were eligible, 53 were excluded and 147 patients with long COVID were included. QoL was evaluated across eight domains using the 36-Item Short Form Health Survey (SF-36). Standardized protocols including the Beck Anxiety Inventory (BAI) (n = 103), Pittsburgh Sleep Quality Index (PSQI) (n = 73), and Migraine Disability Assessment (MIDAS) (n = 67) were also used. Results Participants with sleep disorders had significantly lower Vitality (p < 0.001). Participants with anxiety disorders had significantly lower Vitality (p = 0.001), poorer Mental Health (p = 0.008), and more severe Bodily Pain (p = 0.008). Participants with headache had significantly lower Vitality (p = 0.032), poorer Mental Health (p = 0.036), and poorer Physical Functioning (p = 0.016). Participants with both headache and anxiety had significantly lower Vitality (p = 0.005) and Mental Health (p = 0.043) domain scores. Correlation analysis revealed that higher scores for anxiety, sleep disorder, and headache were independently correlated with poorer QoL across various domains. The presence of sleep disorder was associated with a fourfold increase in risk of experiencing diminished Vitality (odds ratio [OR]4.47; 95% CI 1.01–19.69; p = 0.048). Conclusion Participants with anxiety, sleep, and headache disorders tended to have a worse QoL. The Vitality and Mental Health domains were the most adversely affected in patients with long COVID. Sleep disorders were associated with a fourfold increase in the risk of poor Vitality.